Síntese, caracterização e estudo de complexos de neodímio utilizando curcuminóides como ligantes - Martins, João Fernando Neves (2012)
The complexes of neodymium (Nd(1,7-bis-(hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione)3 (complex 01), Nd(5-hydroxy-1-(4-hydroxy-3-methoxyphenyl)-hexa-1E, 4E-diene-3-one)3 (complex 02), Nd(1,7-diphenyl-hepta-1E,6E-diene-3,5-dione)3 (complex 03) e Nd(5-hydroxy-1,7-bis-(4-hydroxy-3-methoxy-phenyl)-hepta-4E-em-3-one)3) (complex 04) were synthesized, using as binders some derivatives of Curcumin, and characterized by different techniques. Important properties of these complexes were studied and compared with their ligands. The complexes were characterized evidencing the stoichiometry of reactions, formulas and molecular weights. For this we used the techniques of mass spectrometry for time of flight (TOF-MS), elemental analysis (CHN), Thermal Analysis (DSC, TG / DTG) Spectroscopy: FTIR, UV / Visible and X-ray diffraction (XDR). Important properties such as antioxidant, fluorescence, thermal and photochemical stability and crystallinity were checked. The quantum yield of oxidation of the complexes calculated from the chemical suppression constant (shown much larger than the constant physical suppression, kr >> kq), and the rate constant for deactivating singlet oxygen in the solvent (kd) were in the range of 1.99 x 10-2 and 4.14 x 10-2 M-1s-1. The determination of antioxidant potential made by monitoring the decay of the absorbance spectrum of the photo-oxidizable substrate 1,3 - diphenylisobenzofuran (DPBF). In these cases we observe an increase in the antioxidant potential of the complexes compared with their ligands isolated in spite of possessing lower photochemical stability when compared to their ligands isolated. Another important property of the complexes was found to inactivate fecal coliforms, especially Escherichia coli, and this potential is higher as compared with the potential inactivation of Curcumin. This study shows the possibility of prove the antioxidant compounds character curcuminoids by its complexation with Neodymium, the standpoint of drug development. Other important properties as an inhibitor of microorganisms and probe are important from the viewpoint of development of materials in applications as diverse as biofilms and packaging.